The level of active open-minded thinking among Sumer University students and its relationship to their life skills - Ghani, Duaa (Al-Adab Journal, 2024)
The current research aims to reveal the level of active open-minded thinking among Sumer University students and its relationship to their life skills. Therefore, the researcher had to prepare the active open-minded thinking scale, whose paragraphs amounted to (26) items, and the life skills scale, which amounted to (28) items, to identify the level of active open-minded thinking and skills. Life among students of the College of Basic Education Among the results of the research, the arithmetic mean of the students of the College of Basic Education was (57.38) and the standard deviation was (16.08), while the hypothetical mean was (52). The calculated t- is (2.59), which is greater than the tabular value (1.67), and this result indicates that it is statistically significant at the level of significance (0.05), and this means that students have active open thinking, Among the results of the research is also the students' possession of life skills, as the arithmetic mean was (60.50) and the standard deviation was (15.19), while the hypothetical mean was (56). (2.29), which is greater than the tabular value (1.67), and this result indicates that it is statistically significant at the level of significance (0.05, There is also a good direct relationship between students' possession of active open thinking and life skills. In light of this, the researcher recommended the preparation of programs and courses for students that help in developing active open-minded thinking in various disciplines, as well as conducting similar studies concerned with developing counseling programs for developing life skills among students of the College of Basic Education.